MODEL PENGENTASAN KEMISKINAN EKSTREM UNTUK PENCEGAHAN KESENJANGAN SOSIAL DI INDONESIA DALAM PERSPEKTIF SOSIOLOGI DAN HUKUM ISLAM - Fauzi, Fauzi; mahmuddin, Mahmuddin; Juhari, Juhari; Amirulkamar, Said; Hidayati, Ummunisa (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
Abstract: Poverty alleviation and social inequality in Indonesia is a very complex issue overall in various regions in Indonesia Extreme poverty alleviation refers to deliberate efforts aimed at reducing or eliminating extreme poverty, which relates to circumstances in which individuals or households live below the poverty line is so small that they cannot meet their basic needs to survive. This study aims to analyze the extreme poverty alleviation model to prevent social inequality in Indonesia from the perspective of Islamic sociology and law and focuses on reviewing these problems through the perspective of sociology and Islamic law. The qualitative research method is descriptive. Source of data obtained through the official website, mass media, journals, regulations, and books. The data analysis technique uses the Nvivo 12 plus analysis technique which uses the crosstab feature. The results of the study show that the extreme poverty alleviation model that is applied is budgeting and collaboration. Poverty alleviation to prevent social inequality in Indonesia has been carried out by the Government of Indonesia to reduce the poverty rate to 0 percent in the following year. Poverty alleviation in Indonesia through the budgeting system requires the implementation of well-structured and sustainable strategies. Budgeting and collaboration between government and society play an important role in allocating appropriate resources for initiatives and policies aimed at reducing or eliminating extreme poverty. Keywords: Poverty Alleviation, Social Inequality, Sociology, Islamic Law.